Analisis Resistensi Masyarakat Terhdap Pembangunan Waduk Logong di Desa Kandangmas Kecamatan Dawe Kabupaten Kudus - Finda Octafiyanti; Puji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2017)
Abstract. Land is the most important matter in human’s life. Regardless of the activities, humans always need their land. Development, in every aspect, is paramount for society, and in accordance to development, our government has contributed in building public road, markets, dam, and many other in order to fulfill our public concerns. This public development requires vast area to occupy, and considering the requirement, either a land acquisition or retribution by the government should be done under the patronage of our Constitution of 1945. Acquiring available land for public concerns is prior to development process in order to improve prosperity by securing law and rights of the rightful ones. Nevertheless, some negations are still emerging, which means some people might accept and the rest might refuse the governmental proposal.This research uses qualitative approach by collecting some information through interview and documents review. The interviewees are Kepala Dinas Cipta Karya dan Tata Ruang Kabupaten Kudus, Tim Panitia Pengadaan Tanah, Kepala Desa Kandangmas, Ketua Koordinator Forum Komunikasi Masyarakat Korban Embung Logung (Forkomakembung), and Masyarakat Desa Kadangmas Kecamatan Dawe Kabupaten Kudus.The following results show that there are steps of process of Waduk Logung building plan, which are planning and its execution. The process as follows: locating and measuring the target area, establishing committee of area acquirement, funding the building plan, establishing committee of fund appraisal, socializing and holding a conference, acquiring the target area and funding for compensation. The reason behind the public refusal is that there is massive anxiety in the land acquirement and its retribution, communication error, and also the absence of public relation, which all of these cause social, political and economical problems. Our government has tried to overcome this public refusal by applying the theory of conflict and its resolution, which are negotiation, mediation, reconciliation, and arbitration approach, by Marc Galanter. These approaches have been held by our government to console the massive anxiety, yet it did not work as it should be. Thus, our government is reaching for a resolution through adjudication and has been through in consignment.There is a better recommendation for Pemerintah Kabupaten Kudus. Its government, in acquiring land, should be, first of all, socializing the regulations in acquiring land so that its society understands the roles of land in social development, especially in Waduk Logung case. There should be an improved communication between the government and its society, and voices should be heard and be given fast responses in order to avoid unnecessary conflict. Considering the retribution, the committee should let people give their opinions so that there would be a good relation between the government and its society.Key words: Land Procurement, Resistance, Land Acquisition and Indemnification